Key trends in elderly people mortality from the toxic effects of ethanol - M. A. Botova (Здоровье мегаполиса)
This article including an analysis of trends in mortality of the elderly population (from 60 to 75 years, according to the classification of the World Health Organization) to various criteria from ethyl alcohol poisoning. We studied the dynamics of mortality the elderly people from the toxic effects of ethanol, as well as correlations and causal relationships were found between the frequency of death from the indicated cause and gender, age, and the place where the body was found (urban or rural). The features of filling in a medical certificate of death with the initial (presumed) and final cause of death "toxic effects of ethanol" were revealed. The place of direct alcoholic mortality of the elderly population in the total mortality from all causes and ethanol poisoning in the region of the Chelyabinsk region for the period from 2010 to 2021 was determined.